A guide to sports and injury management - Bundy, Mike; Leaver, Andy (Churchill Livingstone Elsevier, 2010)
A Guide to Sports and Injury Management is a comprehensive practical guide to sports medicine care - book plus interactive DVD. Approached from the dual perspectives of a sports medicine doctor and a sports physiotherapist, this exciting new product covers the full spectrum of sports medicine from diagnosis of injuries to injury prevention, techniques for stretching and cooling, protocols, rehabilitation and details on illness, drugs and diet. Colour photographs and drawings support the text, and case histories clearly illustrate the process of making a decision and treating an injury.